Depressive and Anxiety Symptoms in Older Adults With Auditory, Vision, and Dual Sensory Impairment. (September 2019) - Simning, Adam; Fox, Meghan L.; Barnett, Steven L.; Sorensen, Silvia; Conwell, Yeates
Objective: The objective of the study is to examine the association of auditory, vision, and dual sensory impairment with late-life depressive and anxiety symptoms.Method: Our study included 7, 507 older adults from the National Health & Aging Trends Study, a nationally representative sample of U.S. Medicare beneficiaries. Auditory and vision impairment were determined by self-report, and depressive and anxiety symptoms were evaluated by the two-item Patient Health Questionnaire (PHQ-2) and two-item Generalized Anxiety Disorder Scale (GAD-2), respectively.Results: Auditory, vision, and dual impairment were associated with an increased risk of depressive and anxiety symptoms in multivariable analyses accounting for sociodemographics, medical comorbidity, and functional impairment. Auditory, vision, and dual impairment were also associated with an increased risk for depressive and anxiety symptoms that persist or were of new onset after 1 year.Discussion: Screening older adults with sensory impairments for depression and anxiety, and screening those with late-life depression and anxiety for sensory impairments, may identify treatment opportunities to optimize health and well-being.